Solitary Femoral Nodal Metastasis Identified With 68Ga–Prostate-Specific Membrane Antigen PET/CT. (February 2021) - Hilliar, Luke; Yip, Joshua Wei Liang; Wong, Veronica Chi Ken; Le, Ken; Mansberg, Robert
Abstract : Abstract: A 66-year-old man was referred for a 68 Ga–prostate-specific membrane antigen (PSMA) PET/CT scan for primary staging of Gleason 8 prostatic adenocarcinoma. The PET/CT images confirmed PSMA activity in the bilateral prostatic apex in keeping with the known malignancy. An intensely PSMA-avid focus was also noted in a nonenlarged right femoral lymph node with no evidence of PSMA-avid metastatic disease elsewhere. Subsequent core biopsy and histopathology confirmed a solitary metastatic focus of prostatic adenocarcinoma in a right femoral lymph node.